Ethnoveterinary knowledge of farmers in bilingual regions of Switzerland – is there potential to extend veterinary options to reduce antimicrobial use?. (10th January 2020) - Mertenat, Doréane; Cero, Maja Dal; Vogl, Christan R.; Ivemeyer, Silvia; Meier, Beat; Maeschli, Ariane; Hamburger, Matthias; Walkenhorst, Michael
Abstract: Ethnopharmacological relevance: In the pre-antibiotic era, a broad spectrum of medicinal plants was used to treat livestock. This knowledge was neglected in European veterinary medicine for decades but kept alive by farmers. Emergence of multidrug resistant bacterial strains requires a severely restricted use of antibiotics in veterinary medicine. We conducted a survey on the ethnoveterinary knowledge of farmers in the bilingual (French and German speaking) Western region of Switzerland, namely the cantons of Fribourg, Neuchâtel and Jura, and in the French speaking part of the canton of Bern. Aim of the study: To find out whether differences exist in plants used by farmers in French speaking and bilingual regions of Switzerland as compared to our earlier studies conducted in Switzerland. Additional focus was on plants that are used in diseases which commonly are treated with antimicrobials, on plants used in skin afflictions, and on plants used in animal species such as horses, for which the range of veterinary medicinal products is limited. Material and methods: We conducted in 2015 semistructured interviews with 62 dialog partners, mainly cattle keeping farmers but also 18 horse keeping farmers. Of these, 41 were native French (FNS) and 21 native German speakers (GNS). Detailed information about homemade herbal remedies (plant species, plant part, manufacturing process) and the corresponding use reports (target animal species, category of use, route of administration, dosage, source of knowledge, frequency of use, last time of use and farmers satisfaction) were collected. Results: A total of 345 homemade remedies were reported, of which 240 contained only one plant species (Homemade Single Species Herbal Remedy Reports; HSHR). A total of 289 use reports (UR) were mentioned for the 240 HSHR, and they comprised 77 plant species belonging to 41 botanical families. Of these, 35 plant species were solely reported from FNS, 20 from GNS, and 22 from both. Taking into account earlier ethnoveterinary studies conducted in Switzerland only 10 (FNS) and 6 (GNS) plant species connected with 7% of FNS and GNS UR respectively were "unique" to the respective language group. The majority of the UR (219) was for treatment of cattle, while 38 UR were intended to treat horses. The most UR were for treatment of gastrointestinal and skin diseases. The most frequently mentioned plants were Linum usitatissimum L., Coffea L., Matricaria chamomilla L., Camellia sinensis (L.) Kuntze, and Quercus robur L. for gastrointestinal diseases, and Calendula officinalis L., Hypericum perforatum L. and Sanicula europaea L. for skin afflictions. Conclusion: No clear differences were found between the medicinal plants used by French native speakers and German native speakers. Several of the reported plants seem to be justified to widen the spectrum of veterinary therapeutic options in gastrointestinal and dermatological disorders in cattle and horses, and to reduce, at least to a certain degree, the need for antibiotic treatments. Our findings may help to strengthen the role of medicinal plants in veterinary research and practice, and to consider them as a further measure in official strategies for lowering the use of antibiotics. Graphical abstract: Image 1